Translation and Validation of the Tamil Version of the Menopause Rating Scale - Chanil Ekanayake; Sakshara Ranasinghe; Arunasalam Pathmeswaran; Kopalasuntharam Muhunthan (Journal of Mid-Life Health)
Introduction: The Menopause Rating Scale (MRS) is a widely used tool to assess the health-related quality of life (HRQOL) and severity of menopausal symptoms in postmenopausal women. The objective of the present study was to validate a Tamil translation of the MRS, as a Tamil translation is not available. Methods: The Tamil translation of MRS was developed following standard methodology, and a validation study to assess psychometric properties was done at the community level in Mannar, Sri Lanka. Reliability was assessed through internal consistency and test–rest reliability. Validity was assessed using content, discriminatory, and construct validity. Results: Internal consistency using Cronbach’s α coefficient ranged from 0.74 to 0.78 and test–retest reliability assessed by weighted kappa (k) ranged from 0.51 to 0.71. Content validity was evaluated by the acceptability of items for a sample of women and gynecologists conversant in Tamil during the translation process. Discriminant validity between symptomatic and asymptomatic women was significant for all three domains: somato-vegetative, sexual, and psychological (P < 0.05). Factor analysis with exploratory principal component analysis revealed three factors that explained 55.9% of the cumulative variance, demonstrating satisfactory construct validity. A MRS total score ≥6 had a sensitivity of 81% and a specificity of 84.7% to identify symptomatic menopausal women. Conclusion: Tamil translation of MRS retained the psychometric properties of the original questionnaire and will be an invaluable tool to assess menopausal symptoms and HRQOL among postmenopausal tamil-speaking women.